Minors, Disabilities, School: What Is True Inclusion Through the Life Project? (TEST BioLaw Journal - Rivista di BioDiritto, 2026)
This article analyzes the Life Project as a key tool for the effective implementation of the rights of persons with disabilities, with particular reference to childhood and the school context. Starting from the recent introduction of Legislative Decree No. 62/2024, it highlights how this institution constitutes not only an operational projection of the bio-psycho-social paradigm, but also a legal safeguard for personalized inclusion. The investigation, which is theoretical-legal and constitutionally oriented, focuses on the relationship between the Life Project and the PEI, questioning its actual enforceability and the need for a regulatory and procedural framework that guarantees its concrete implementation as a fully protectable subjective right.
Keywords: disability; inclusive education; individualized education plan; life plan; customization